2015
DOI: 10.1021/jacs.5b07913
|View full text |Cite
|
Sign up to set email alerts
|

Release of Native-like Gaseous Proteins from Electrospray Droplets via the Charged Residue Mechanism: Insights from Molecular Dynamics Simulations

Abstract: The mechanism whereby gaseous protein ions are released from charged solvent droplets during electrospray ionization (ESI) remains a matter of debate. Also, it is unclear to what extent electrosprayed proteins retain their solution structure. Molecular dynamics (MD) simulations offer insights into the temporal evolution of protein systems. Surprisingly, there have been no all-atom simulations of the protein ESI process to date. The current work closes this gap by investigating the behavior of protein-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
176
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(183 citation statements)
references
References 87 publications
6
176
1
Order By: Relevance
“…45 Briefly optimized structures often have CCS values matching well with the experiments. 42,[46][47][48] Fabris and co-workers have recently underlined the difficulties in transposing to DNA the MD and CCS calculation protocols traditionally used for proteins. 43 As a way out they proposed to calibrate all traveling wave IMS data using short MD simulation results, but our study shows why this approach would lead to a misrepresentation of nucleic acid structures in the gas phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Briefly optimized structures often have CCS values matching well with the experiments. 42,[46][47][48] Fabris and co-workers have recently underlined the difficulties in transposing to DNA the MD and CCS calculation protocols traditionally used for proteins. 43 As a way out they proposed to calibrate all traveling wave IMS data using short MD simulation results, but our study shows why this approach would lead to a misrepresentation of nucleic acid structures in the gas phase.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the resulting charge density is similar to those observed experimentally from native conditions. It is therefore likely that the DNA duplexes are desolvated via the charged residue model 41,42 and that the compaction results from the association of NH 4 + cations to both minor and major groove before full desolvation. As a result, the starting structure for gas phase simulations might be quite different to the canonical A-or B-helices.…”
Section: ) Progressive Duplex Desolvation Leads To Experimentally Rementioning
confidence: 99%
“…An in-house Fortran program was used for electrostatic mapping. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 It is not clear from the literature 41,53 to what extent nonspecific metal adducts affect the structures of globular proteins under gentle ESI conditions. Figure 2A shows that Ω values of [Ubq + 6H] 6+ , [Ubq + 6Na] 6+ , and [Ubq + 3Ca] 6+ differ by no more than 2%.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…For example, ESI of NaCl-containing protein solutions generates heterogeneous [M + zH + n(Na-H) + m(Cl+H)] z+ assemblies. [52][53][54] It has been reported that non-specifically bound small ions can stabilize collisionally activated multi-protein complexes, i.e., they shift the onset of CID to higher collision energies. 37 Anions that dissociate from the protein as protonated neutrals can lower the internal energy of the analyte by evaporative cooling.…”
mentioning
confidence: 99%
“…Furthermore, the molecule must be removed from solvent and ionized (or allowed to retain a net charge) in order to be observed. Typically this is achieved with electrospray ionization (ESI); however, mechanistic details for ESI are not completely understood and it is unclear how protein structure evolves during electrospray, although recent progress has been made [24,25]. Ultimately, results have been reported where native protein structure is either retained or lost upon examination in the gas phase [26,27].…”
mentioning
confidence: 99%